PERANAN PSIKOLOGI FORENSIK PADA KASUS HUKUM UNTUK KORBAN KRIMINAL: SEBUAH TINJAUAN LITERATUR - Muhammad Farid Alifianto; Adinda Khoirunnisa Nur; Difani Cahya Prastiwi; Tugimin Supriyadi (Cahaya Ilmu Bangsa Institute, 2024)
Forensic psychology plays a crucial role in law enforcement processes, particularly in supporting victims of crimes through psychological approaches. This study aims to analyze the contribution of forensic psychology in legal cases and the challenges of its implementation in Indonesia. The method used is a literature review by identifying and evaluating various scientific sources related to the topic. The results show that forensic psychology contributes to criminal profiling, assessing the mental condition of victims, and providing expert testimony in court. However, regulatory limitations and a lack of understanding among law enforcement officials are the main barriers to its implementation. Key recommendations include increasing cross-sector collaboration and training for law enforcement personnel to optimize the role of forensic psychology.